Editorial. Mobile learning during the era of COVID-19 - Al-Emran, Mostafa (Revista Virtual Universidad Católica del Norte, 2020)
A novel coronavirus (COVID-19) has been identified in Wuhan, China, in late 2019 (Zhu et al., 2020). On March 11, 2020, the World Health Organization (WHO) has declared the outbreak of COVID-19 as a global pandemic (Cucinotta & Vanelli, 2020). In responding to this pandemic, a series of precautionary measures have been taken forward on a global basis to combat the spread of the virus. One of such measures was the lockdown of educational institutions. To compromise between the delivery of learning to students and committing to social distancing, the transition to distance learning was the unavoidable option in such crises.